Tingkat Efisiensi Perhitungan Kolom Beton (Perbandingan PBI 1971 Dengan SNI 1991) - Nuryati, Sri; Suwanto, Sigit (Universitas Islam 45, 2019)
The collapse of a column causes the collapse of the entire building that need a large cost for repairing. Therefore, special attention is needed when planning the columns, i.e. by providing a backup strength on columns which greater than other beams and other horizontal structural elements since there is no initial warning in a press-type of collapse. This study aims to determine the efficiency of square concrete column dimensions in case of column calculations after the revision of PBI 1971 to SNI 1991 standard both by manual calculation and using the Turbo Pascal-based application. Calculation utilized the elastic method and ultimate method with the assumption that column conditions are similar as well as the column data is taken from the calculation of reinforced portal structures. Concrete columns are made rectangle with dimensions of size 35 x 35 cm and size 75 x 75 cm, concrete quality K 225, steel quality U24 (2400 kg / cmÂ²), modulus of steel elasticity 2.1. 10â¶ kg / cmÂ² and 5 cm thick of concrete blanket, with the assumption that structural analysis has been conducted for calculating the boundary and moment loads, assuming that the column conditions are similar. In case of the ability to retain the load and moment by the column, assuming the constant area of â€‹â€‹reinforcement in various dimensions, the results of the elastic method (PBI 1071) were smaller than the ultimate method (SK SNI 1991). The calculation results showed that the ultimate method was more efficient than the elastic method in terms of the efficiency of reinforcing steel use.